Adult Cardiac-Related Deaths: A Reflection of Epidemiologic Transition of Diseases in the Developing World? - Thomas, Martins O.; Awolola, Nicholas A.; Olusoji, Olugbenga O. (Scientific Research, 2012)
Background: Epidemiologic transition of diseases is taking place globally. Therefore, it is necessary that more work is done to unravel the situation in respect to cardiac diseases in the developing world. Aim: The research was conducted to ascertain the cardiac causes of death in adults and by extension to further unravel the epidemiologic transition in relation to cardiac diseases in the developing world. Materials and Methods: This is an autopsy study of adult cardiac related causes of death in the year 2010 at the Lagos University Teaching Hospital in Nigeria, West Africa. It was conducted based in a 700-bedded hospital that has a catchment area of about 15 million people. Patients’ data (including bio-data, causes of death, etc.) were extracted from autopsy records for the year 2010. The data were entered and analysed with SPSS software. Results: There were 789 autopsies in the year and 99 of deaths were cardiac-related. There was male preponderance with a mean age of 54.2 ± 1.568 years. Hypertensive heart disease was the primary disease in 97.0% of cases in the studied sample. One 76 year old adult had myocardial infarction. There was no case of adult congenital heart disease. Intracerebral haemorrhage was the commonest cause of death. Discussion and Conclusion: Cardiovascular diseases constitute a growing threat to health among Africans. The developing countries are in stages II and III of Omran epidemiologic transition of diseases. This presents a major challenge to a large proportion of the world population with additional problem of poverty and ignorance. A 4-point agenda is suggested to reduce incidence of cardiovascular diseases (and deaths) in the developing world.
Keywords: Cardiac; Deaths; Disease; Transition